Williams' expansion‐based approximation of the displacement field in an Al 2024 compact tension specimen reconstructed from optical measurements. Issue 10 (16th May 2018) - Seitl, S.; Malíková, L.; Růžička, V.; Moreno, B.; Lopez‐Crespo, P.
Abstract: A study on the approximation of the displacement field in the vicinity of a crack tip in a compact tension specimen made from Al 2024‐T351 is presented. Components of displacements vector are expressed using the linear elastic fracture mechanics theory via Williams' power series multi‐parameter formulation. Determination of the coefficients of the terms of this series is performed using a least squares‐based regression technique known as over deterministic method for which displacements data obtained experimentally via optical measurements are taken as inputs. The displacement fields reconstructed are discussed, and several conclusions are drawn regarding the number of the Williams' power series terms considered and the region where the displacement are investigated.